Pengaruh Riwayat Infeksi Covid-19 dengan Kejadian Ikutan Pasca Imunisasi Moderna - Irene Setiawan; Olivia Paulus; Yohanes Firmansyah; Hendsun Hendsun (Jurnal Kesehatan, 2022)
Introduction: SARS CoV-2 is a virus categorized by the World Health Organization (WHO) as Variants of Concern (VoC) where this category indicates an increase in transmission or an epidemiologically adverse change, an increase in virulence or a change in the presentation of clinical disease, a decrease in public health effects in the form of diagnostics, vaccines and therapy. Objective: To determine the effect of a history of COVID-19 infection with mild or severe degrees of AEFI. Methods: This research is cross-sectional. Statistical analysis using Chi-square with Yates Correction statistical test. Results: From the questionnaire results obtained PIAE in the form of pain at the injection site, redness at the injection site, dizziness, fatigue, muscle aches, fever, nausea and vomiting. From a total of 64 respondents, 34 respondents who had been infected with COVID-19, the symptoms of booster vaccination were felt lighter in 3 (8.8%) and more severe in 31 (91.2%) respondents. Meanwhile, the other 30 respondents who had never been infected with COVID-19 were lighter in 1 (3.3%) and heavier in 29 (96.6%) respondents. Statistical test results with Pearson Chi-Square showed a non-significant relationship between a history of COVID-19 infection and the severity of symptoms of booster vaccination (p-value: 0.365). Conclusion: COVID-19 infection does not affect the mild or severe severity of PIAE in young adult respondents. Research is needed with a larger number of respondents followed by a randomized model.